Molecular Insights Into Regulatory T-Cell Adaptation to Self, Environment, and Host Tissues: Plasticity or Loss of Function in Autoimmune Disease - Brown, Cheryl Y.; Sadlon, Timothy; Hope, Christopher M.; Wong, Ying Y.; Wong, Soon; Liu, Ning; Withers, Holly; Brown, Katherine; Bandara, Veronika; Gundsambuu, Batjargal; Pederson, Stephen; Breen, James; et al. (Frontiers in Immunology, 2020)
Regulatory T cells (Treg) are critical for preventing autoimmunity, by curtailing conventional effector T cell (Tconv) responses. The dependence of Treg on the master transcription factor FOXP3 for formation and function reveals the importance of lineage shaping transcription factors in setting cell fate. There has been much interest in the ability of Treg to switch function in vivo, either as a result of genetic risk of disease, or in response to environmental and metabolic cues. The relationship between levels of FOXP3 and functional fitness plays a significant part in this plasticity. There is an emerging role for Treg in tissue repair that may be less dependent on FOXP3, but the molecular mechanisms underpinning this are not fully understood. As a result of detailed, high resolution functional genomics, the gene regulatory networks and key functional mediators of Treg phenotype downstream of FOXP3 have been mapped, enabling a mechanistic insight into Treg function. This transcription factor-driven programming of T cell function to generate Treg requires switching on and off of key genes that form part of the Treg gene regulatory network, and raises the possibility that this is reversible. It is plausible that subtle shifts in expression levels of specific genes, including transcription factors and non-coding RNAs, changes regulation of the gene regulatory network. The subtle skewing of gene expression initiates changes in function, with the potential to promote chronic disease, and/or to license appropriate inflammatory responses. The interplay of genetic and environmental cues is complex, and impacts gene regulation networks operating over long distances, frequently involving promoters and enhancers, the regulatory elements that control gene expression levels and responsiveness. In autoimmunity, altered Treg/Tconv function may be influenced by changes in these enhancer /promoter interactions, which are highly cell type specific. Genetic risk may cause the subtle alterations to the responsiveness of gene regulatory networks which are controlled by or control FOXP3 and its target genes. Connection of non-coding regulatory regions to the genes they control, is revealing the direct impact of environmental/ metabolic /genetic risk on T cell function and providing mechanistic insight into susceptibility to inflammatory and autoimmune conditions.